Consumption as an identity-creator - Prónay, Szabolcs (The Hungarian Journal of Marketing and Management, 2019)
Marketing usually brings in from other theoretical disciplines. This study attempts to do so, in which a specific area of economical psychology, namely identity research, is compared to consumer behaviour. The study is based on László Garai’s theory. From this perspective it links identity creation to consumption especially brand choice, brand communities and loyalty -, trying to find the connection between identity and consumer choice.